2022
DOI: 10.26905/afr.v5i2.7530
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Whistlebowing System toward Fraud Prevention: Mediation of Forensic and Investigative Audit

Abstract: This study aims to determine the effect of whistleblowing system toward fraud prevention with forensic audit and investigative audit as a mediating variable. The population of this study are auditor in Inspectorate of Banten Province. The result of this study indicates that first, whistleblowing system partially have a positive significant effect on the forensic audit. Second, whistleblowing system partially have a positive significant effect on the investigative audit. Third, whistle-blowing system partially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…According to Hanifah and Clyde (2022), this circumstance gives WBS the chance to minimize and reduce the opportunities that fraudsters have. WBS exists in an entity, and fraudsters may also feel the dread effect (Siregar et al, 2022).…”
Section: H6: Collusion Has An Effect On Financial Statement Fraudmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Hanifah and Clyde (2022), this circumstance gives WBS the chance to minimize and reduce the opportunities that fraudsters have. WBS exists in an entity, and fraudsters may also feel the dread effect (Siregar et al, 2022).…”
Section: H6: Collusion Has An Effect On Financial Statement Fraudmentioning
confidence: 99%
“…It is anticipated that having a WBS will assist organizations in making sure that fraudsters change their minds. WBS can serve as both an early warning system and a detector for fraud risk (Hanifah & Clyde, 2022). In addition, WBS participants welcome members of the public at all societal levels who would like to report instances of fraud within an organization.…”
Section: Wbs Weakens Pressure On Financial Statement Fraudmentioning
confidence: 99%
“…This study employed multi regression tool, and revealed that such effect or influence significantly exists. Clyde et al (2022) is another study that applied survey design, and Partial Least Square (PLS) technique to find, among others, that a "partial" positive significant effect exist between WB-S and fraud prevention. Emeka-Nwokeji et al ( 2019) rather utilized the descriptive statistics of sample t-test, and Pearson Product Moment Correlation Coefficient to reveal that WB-S is a significant tool for reducing fraudulent activities; and found a significant relationship to exist between WB-S alongside its legislation, and fraud prevention and detection in public companies.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…Hal ini menunjukkan adanya hubungan positif antara whistleblowing dan audit forensik. Penelitian yang sejalan dengan uraian tersebut adalah penelitian yang dilakukan oleh (Clyde & Hanifah, 2022) (Rahmida & Urumsah, 2020), dan (Daurrohmah et al, 2021) yang menyatakan bahwa penerapan whistleblowingsystem terbukti berpengaruh signifikan terhadap audit forensik.…”
Section: Pendahuluanunclassified